ESTIMATION OF BLOCK :RO" SHALE GAS DISTRIBUTION ON SOUTH SUMATRA BASIN - RIZALDI , OKI
The energy demands is increasing from time to time, this energy demand can not be fulfilled if only relying on hydrocarbon resources which obtained through the conventional methods that exist today, hence the exploration and exploitation of hydrocarbon resources using non-conventional method start to be developed and applied to meet the high energy demands. One of a kind of hydrocarbons obtained through non-conventional means is shale gas, the shale gas basically is a natural gas which generated and trapped in shale-size rock, with high organic carbon content and already in the gas maturity window, so that in shale gas the hydrocarbons was formed and trapped on the same rock without having to migrate to the reservoir rocks as conventional hydrocarbons method.South Sumatra Basin formed on Eocene Ã‚Â– Recent age, some shale intervals in this basin has been proven to be the source rock for several oil and gas fields in the vicinity, this condition makes the shale layers are attractive for the development of shale gas exploration. The biggest challenge in the development of shale gas in Indonesia is the lack of reference to shale gas fields that have been in production in Indonesia, so the dataset and the results of a comprehensive study on shale gas Indonesia is still very rare, in addition to the variation in shale gas layer either vertically or laterally further increase the level of uncertainty in studying the shale gas.